Radiofrequency Ablation for Chronic Low Back Pain: A Systematic Review of Randomized Controlled Trials. (2014) - Leggett, Laura E; Soril, Lesley JJ; Lorenzetti, Diane L; Noseworthy, Tom; Steadman, Rodney; Tiwana, Simrandeep; Clement, Fiona
Abstract : BACKGROUND: Radiofrequency ablation (RFA), a procedure using heat to interrupt pain signals in spinal nerves, is an emerging treatment option for chronic low back pain. Its clinical efficacy has not yet been established. OBJECTIVE: To determine the efficacy of RFA for chronic low back pain associated with lumbar facet joints, sacroiliac joints, discogenic low back pain and the coccyx. METHODS: A systematic review was conducted. Medline, EMBASE, PubMed, SPORTDiscus, CINAHL and the Cochrane Library were searched up to August 2013. Abstracts and full-text articles were reviewed in duplicate. Included articles were sham-controlled randomized controlled trials (RCTs), assessed the efficacy of RFA, reported at least one month of follow-up and included participants who had experienced back pain for at least three months. Data were extracted in duplicate and quality was assessed using the Cochrane Risk of Bias tool. Due to heterogeneity, as well as a lack of reported mean differences and SDs, meta-analysis was not possible using these data. RESULTS: The present systematic review retrieved 1063 abstracts. Eleven sham-controlled RCTs were included: three studies involving discogenic back pain; six studies involving lumbar facet joint pain; and two studies involving sacroiliac joint pain. No studies were identified assessing the coccyx. The evidence supports RFA as an efficacious treatment for lumbar facet joint and sacroiliac joint pain, with five of six and both of the RCTs demonstrating statistically significant pain reductions, respectively. The evidence supporting RFA for the treatment of discogenic pain is mixed. CONCLUSIONS: While the majority of the studies focusing on lumbar facet joints and sacroiliac joints suggest that RFA significantly reduces pain in short-term follow-up, the evidence base for discogenic low back pain is mixed. There is no RCT evidence for RFA for the coccyx. Future studies should examine the clinical significance of the achieved pain reduction and the long-term efficacy of RFA.